2015
DOI: 10.1111/tbj.12455
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Long-term Study of a Large Series of Patients with Invasive Ductal Carcinoma and Invasive Lobular Carcinoma. Loco-Regional Recurrence, Metastasis, and Survival

Abstract: Our aim was to compare histologic and immunohistochemical features, surgical treatment and clinical course, including disease recurrence, distant metastases, and mortality between patients with invasive ductal carcinoma (IDC) or invasive lobular carcinoma (ILC). We included 1,745 patients operated for 1,789 breast tumors, with 1,639 IDC (1,600 patients) and 145 patients with ILC and 150 breast tumors. The median follow-up was 76 months. ILC was significantly more likely to be associated with a favorable phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…In a sample of 75 lobular tumors from the I-SPY trial, Lips et al (2012) determined PAM50 subtypes and reported an RFD of 44% for Luminal A subtype among lobular compared to ductal tumors, similar to our findings [50]. Other studies using IHC have reported RFDs for Luminal A subtype among lobular compared to ductal tumors ranging from 6 to 39%, reflecting tremendous molecular variability in the tumors studied [14, 16, 19, 22, 37, 4749, 51, 52]. Proportions of Luminal A ductal tumors were also different between IHC subtype and RNA subtype data, suggesting RNA subtyping may be important for understanding associations between intrinsic subtype and histology.…”
Section: Discussionsupporting
confidence: 83%
“…In a sample of 75 lobular tumors from the I-SPY trial, Lips et al (2012) determined PAM50 subtypes and reported an RFD of 44% for Luminal A subtype among lobular compared to ductal tumors, similar to our findings [50]. Other studies using IHC have reported RFDs for Luminal A subtype among lobular compared to ductal tumors ranging from 6 to 39%, reflecting tremendous molecular variability in the tumors studied [14, 16, 19, 22, 37, 4749, 51, 52]. Proportions of Luminal A ductal tumors were also different between IHC subtype and RNA subtype data, suggesting RNA subtyping may be important for understanding associations between intrinsic subtype and histology.…”
Section: Discussionsupporting
confidence: 83%
“…This corresponds well with recent findings of Garcia-Fernandez A et al [39] who found at a median follow-up of 76 months a recurrence rate of 4% vs. 3.2% for invasive-ductal and invasivelobular breast cancer (p ¼ n.s.). Also in their study, lobular histology was more frequently associated with re-excision and/or mastectomy.…”
Section: Discussionsupporting
confidence: 91%
“…18 Data analysis from the COMICE trial did not find statistically significant differences between tumor cell type and the detection of additional lesions on MRI. 10 Because ILC has been previously recognized as having a higher likelihood of multifocal, multicentric, and contralateral breast cancers than cancers of ductal origin, 19,20 that there were high rates of false-positivity associated with the identification of lesions by MRI alone. For example, 60.3% of multifocal lesions that were biopsied were not malignant.…”
Section: Factors Associated With Detection Of Occult Cancermentioning
confidence: 99%